Immunomodulatory MicroRNAs in cancer: targeting immune checkpoints and the tumor microenvironment. (27th July 2019) - Omar, Hany A.; El‐Serafi, Ahmed T.; Hersi, Fatema; Arafa, El‐Shaimaa A.; Zaher, Dana M.; Madkour, Mohamed; Arab, Hany H.; Tolba, Mai F.
Abstract : Cancer immunotherapy represents a promising new era in cancer management due to the relatively high safety margins and selectivity, compared to the classical cancer chemotherapeutic agents. However, there is an imperative need to overcome tumor resistance in order to improve clinical outcomes and maximize the benefits of cancer immunotherapy. The interaction between the programmed cell death‐1 (PD‐1) receptor and its ligand PD‐L1 is a vital immune checkpoint that is often adopted by cancer cells to undergo immune evasion. PD‐1/PD‐L1 signaling is regulated at multiple levels through the crosstalk with other immune targets or relevant signaling partners involved in the cancer progression. Among the significant epigenetic players that are implicated in modulating the immune system are microRNAs (miRNAs). A complex system of these noncoding RNAs regulates the gene expression at the post‐transcriptional level and plays a significant role in the modulation of both innate and the adaptive immune systems. The expression profile of immune‐modulatory miRNAs might be useful as a predictive biomarker for the response and clinical outcomes in cancer immunotherapy. Therefore, in the current review, we highlighted the role of miRNAs in cancer immune evasion through a critical discussion of their impact on key immune checkpoints as well as the role of miRNAs in cancer progression and resistance. Abstract : The expression profile of microRNAs (miRNAs) has a crucial role in the regulation of immune cells function, cancer development, and progression. Thus, immune‐modulatory miRNAs might serve as a predictive biomarker for the response and clinical outcomes in cancer immunotherapy. This work critically highlights the role of miRNAs in cancer immune evasion and their impact on key immune checkpoints as well as their role in cancer progression and resistance to therapy.